How to blow up a pipeline : learning to fight in a world on fire - Malm, Andreas, 1977- (Verso, 2021)
"In this lyrical manifesto, noted climate scholar Andreas Malm makes an impassioned call for the climate movement to escalate its tactics in the face of ecological collapse"--